Chronic granulomatous invasive fungal rhinosinusitis in Nigeria: challenges of management - Asoegwu, Chinyere N.; Oladele, Rita O.; Kanu, Okezie O.; Nwawolo, Clement C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic granulomatous invasive fungal rhinosinusitis affects mainly immunocompetent patients and has been widely reported in tropical regions such as South East Asia and North Africa. Nigeria has a tropical climate, however, there is paucity of data on this disease condition in Nigeria. This study documents the clinical, diagnostic, therapeutic challenges of managing patients with this condition in Nigeria. Methods: A retrospective study of patients diagnosed and treated for chronic granulomatous invasive fungal rhinosinusitis between 2010 and 2019. Diagnosis was based on clinical presentation, computed tomographic scan findings and confirmed by histopathology and/or microbiology results. Results: Ten patients aged 12 to 49 years with mean age of 33.9±13.8 years were studied. Male to female ratio was 2.3:1. All were immunocompetent. Duration of symptoms before presentation ranged from 3 months to 8 years with a mean duration of 3.5±2.4 years. Commonest clinical presentation was unilateral proptosis 80% followed by nasal mass 50%. Commonest sinus involved was the ethmoid (80%). There was orbital extension in 70% and intracranial involvement in 50%. Aspergillus species was the commonest fungal agent cultured. Treatment was by surgical excision followed by antifungal drugs. Some of the challenges we encountered in the management included; late presentation, delay in diagnosis, limited experience in histopathologic and mycology diagnosis and high cost of treatment amidst scarce resource. Conclusions: Chronic invasive granulomatous rhinosinusitis is not rare in Nigeria. A high index of suspicion is however needed for the diagnosis. Development of a National management protocol for this disease is recommended to avoid misdiagnosis.